COST-BENEFIT ANALYSIS OF A SYSTEM OF NON- IDENTICAL UNITS UNDER PREVENTIVE MAINTENANCE AND REPLACEMENT - Malik, S.C.; Upma (Journal of Reliability and Statistical Studies, 2020)
A stochastic model for a system of two non-identical units is developed by considering all random variables statistically independent. Initially, the main unit (original) is operative while the other unit (duplicate) is kept as spare in cold standby. Each unit has two modes – operative and complete failure. A single server is provided immediately to handle the faults which occur during operation of the system. The maintenance and repair of the main unit are carried out whenever needed. However, replacement of the duplicate unit is made by new one after its failure. The failure time and the time by which unit undergoes for preventive maintenance and replacement follow negative exponential distribution, whereas the distributions for preventive maintenance, repair and replacement rates are taken as arbitrary with different probability density functions. Some reliability measures of vital significance are obtained in steady state using semi- Markov process and regenerative point technique. The cost - benefit analysis of the system model has been done for arbitrary values of the parameters. The graphical behavior of some important reliability measures including profit function has been observed.